Influence of moisture content in electrokinetic remediation process of contaminated soil - Nik Daud, Nik Norsyahariati; Hong, K. C.; Azmi, J. A. G. (IET (IEEE Xplore), 2014)
The present legislation has established a legal frame to protect the soil from potentially contaminant activities. However, the current situation of soil is bad due to the past bad practices which had placed the soil in utmost critical condition. This project aims to assess the effect of soil moisture content on electrokinetic remediation of contaminated soil. The potential contaminated soil was obtained from landfill site. In this study, the physical, chemical and mechanical properties of soil sample were carried out in laboratory scale. The initial moisture content of soil were prepared at 15, 30, 45 and 70% to simulate normal field conditions. Nitric acid was used as the cathodic purging solution in electrokinetic cell and sample is remediated for 72 hours at constant voltage of 30V. Results showed that copper and zinc showed different behaviour in soil cover by depth. Concentration of copper increased with depth whereas concentration of zinc decreased with depth. Through electrokinetic remediation process, it was found that the removal efficiency of contaminants in contaminated soil is independent of moisture content of the soil. It showed similar percentage of removal which ranges from 20 to 30%.